The Communication Channels and their Potential Applicability in Enhancing Agricultural Research Data Sharing among Agricultural Researchers in Tanzania - Mwinami, Nolasko; Dulle , Frankwell W.; Mtega, Wulystan Pius (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2023)
The goal of this research was to investigate the communication channels that enhance data sharing among agriculture researchers in Tanzania. Specifically, the study aimed to identify communication channels that are used by agricultural researchers in Tanzania, examine the extent to which such channels were used to enhance data sharing among agricultural researchers, and examine the factors that influence the choices of channels used in data sharing. A descriptive cross-sectional design, alongside quantitative, and qualitative approaches, was employed to collect data from 204 respondents. The Concentric Layered Model for the channel choices was used to guide this study.  Results indicate that both mediated, and non-mediated channels existed and were used as data-sharing avenues and channels. The majority of the researchers (77.9%) preferred to use non-mediated channels. Also, the findings indicate that more than 50% of respondents agreed that timely delivery, the cost of the channel, and convenience of a channel were among the factors influencing researchers in their channel selection. It can be concluded therefore that research institutions should invest in mediated channels that have been underutilized to strengthen data-sharing practices among researchers.